Effects of light and noise pollution on avian communities of European cities are correlated with the species’ diet - Morelli Federico; Tryjanowski Piotr; Ibáñez-Álamo Juan Diego; Díaz Mario; Suhonen Jukka; Pape Møller Anders; Prosek Jiri; Moravec David; Bussière Raphaël; Mägi Marko; Kominos Theodoros; Galanaki Antonia; et al. (Nature Research, 2025)
Urbanization affects avian community composition in European cities, increasing biotic homogenization. Anthropic pollution (such as light at night and noise) is among the most important drivers shaping bird use in urban areas, where bird species are mainly attracted by urban greenery. In this study, we collected data on 127 breeding bird species at 1349 point counts distributed along a gradient of urbanization in fourteen different European cities. The main aim was to explore the effects of anthropic pollution and city characteristics, on shaping the avian communities, regarding species’ diet composition. The green cover of urban areas increased the number of insectivorous and omnivorous bird species, while slightly decreasing the overall diet heterogeneity of the avian communities. The green heterogeneity—a measure of evenness considering the relative coverage of grass, shrubs and trees—was positively correlated with the richness of granivorous, insectivorous, and omnivorous species, increasing the level of diet heterogeneity in the assemblages. Additionally, the effects of light pollution on avian communities were associated with the species' diet. Overall, light pollution negatively affected insectivorous and omnivorous bird species while not affecting granivorous species. The noise pollution, in contrast, was not significantly associated with changes in species assemblages. Our results offer some tips to urban planners, managers, and ecologists, in the challenge of producing more eco-friendly cities for the future. © 2023, The Author(s).